(untitled) (Global Journal of Science Frontier Research, 2022)
The article proves the dialectical unity of the processes of evolution and involution in biological systems due to the simultaneous flow of which the process of their aging slows down and the duration of the reproductive period increases The strengthening of the role of such opposite processes as the systems become more complex is the essence of the basic law of their evolution which eliminates the glaring contradiction of thermodynamics with biological evolution A more general energy-dynamic theory of biosystems is presented which takes into account their heterogeneity with the help of additional parameters of their non-equilibrium The theory returns to thermodynamics the concepts of force speed and power of real processes and supplements the theory of irreversible processes by taking into account the reversible component of real processes The unity of energy conversion processes in technical and biological systems is proved Simpler non-entropy criteria for the evolution and involution of biosystems are proposed for each degree of freedom inherent in it It is shown that relaxation processes in some degrees of freedom of biosystems are accompanied by the performance of work against equilibrium in other degrees of freedom which is the essence of the Darwinian struggle for existence The connection of the mentioned law of evolution with other theories of evolution is discussed and a conclusion is made about its correctness